Evidence-Based Nursing Practice Barriers in ICU - Badriya Al-lenjawi; Jibin Kunjavara; Nesiya Hassan; Kamaruddeen Mannethodi; Ederlie Martinez; George V. Joy; Kalpana Singh (New Horizons in Medicine and Medical Research Vol. 8, 2022)
The current study aimed to examine barriers influencing evidence-based Practice among critical care nurses in Qatar. The Barriers to Research Utilization Scale(BTRUS) was used to collect data from 278 nurses from February to March 2021 via a cross-sectional survey . The BTRUS included information on different information sources used by nurses for practise support, potential impediments to evidence-based practise, and perceived competencies in applying research-based evidence. Lack of time, lack of empowerment to modify Practice, lack of support from colleagues in integrating research evidence, and lack of access to research papers were the most important organisational impediments. The relevance of research data to present practise, studies with methodological faults, scepticism about research conclusions, a significant amount of research evidence, and inability to understand statistics were all identified as self-perceived impediments. Self-reported barriers and use of evidence sources were influenced by the Nurse’s age, years of nursing practise, academic attainment, and organisational position. Organizational support, improved self-belief, and evidence-based practice expertise may reduce barriers to implementing research evidence in clinical Practice. Nursing administrators and educators have the leading role in facilitating evidence-based practice implementation among nurses. Therefore, training and education are essential to enhance the knowledge and skills of nurses to use evidence-based Practice. Time management, providing the required resources, and adequate supervision can facilitate the implementation of evidence-based Practice, which positively influences the quality of care.